2019
DOI: 10.1115/1.4041574
|View full text |Cite
|
Sign up to set email alerts
|

A Design Method to Improve End-of-Use Product Value Recovery for Circular Economy

Abstract: Circular economy (CE) is being increasingly accepted as a promising sustainable business model, supporting waste minimization through product life cycles. The product end-of-use (EOU) stage is the key to circulate materials and components into a new life cycle, rather than direct disposal. The economic viability of recycling EOU products is significantly affected by designers' decisions and largely determined during product design. Low economic return of EOU value recovery is a major barrier to overcome. To ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 22 publications
0
33
0
1
Order By: Relevance
“…Sensors on the product and its production lines as well as more powerful simulations will generate unprecedented volumes of data. Principles of circularity and sustainability will become commercial and moral imperative (Tukker 2015;Man & Strandhagen 2017;Cong, Zhao & Sutherland 2019;Wichmann et al 2019). All this requires greater transparency in the ways of working and greater collaboration with other fields; and therefore, engagement with their tools and methods and ideally a coordination across different disciplines to assure that gaps and incompatibilities do not cause inefficiencies and product failures.…”
Section: /22mentioning
confidence: 99%
“…Sensors on the product and its production lines as well as more powerful simulations will generate unprecedented volumes of data. Principles of circularity and sustainability will become commercial and moral imperative (Tukker 2015;Man & Strandhagen 2017;Cong, Zhao & Sutherland 2019;Wichmann et al 2019). All this requires greater transparency in the ways of working and greater collaboration with other fields; and therefore, engagement with their tools and methods and ideally a coordination across different disciplines to assure that gaps and incompatibilities do not cause inefficiencies and product failures.…”
Section: /22mentioning
confidence: 99%
“…Ma & Kremer (2015) provided a systematic method for evaluating the EOL options of components considering the sustainability and subjective perception of the designer's sustainability. Cong, Zhao & Sutherland (2019) proposed a methodology to determine recovery strategies for end-of-use components and optimal new product design to improve product recyclability for circular economy. Wang et al (2017) showed the impact of component commonality decisions in product family design on component reuse in remanufacturing with respect to introduction time of the second generation of product family and durability of components.…”
Section: Confirmation With the Literaturementioning
confidence: 99%
“…Lastly, design scholars studied the concept of design for value recovery, which looks at ways in which design can work with materials to retain and make better use of their value. Several papers looked at design methods to facilitate value recovery [80]. Mont [81] focused on product durability and researched various design methods to lengthen the product lifespan (e.g., design that can be upgraded or reused, easily maintained, replaced; design for remanufacturing; design for upgrading; mass-customization; timeless design) and strategies that can maximize the utilization rate of consumer durables (e.g., shift from consumer ownership to producer ownership; shift from supply chain to value chain actor-networks).…”
Section: Design For Circular Production Processesmentioning
confidence: 99%
“…Haug [82] described "resilient design" with a fine-grained classification of both causes of product replacement and organizing means to extend the longevity of products. Cong et al [80] suggested a method to improve end-of-use product recyclability through a sequence of steps that evaluate various end-of-use scenarios and then analytically define which components of a product are more suitable to be disassembled, recycled, and reused. Goldsworthy [83] proposed to take into account the multiple rhythms and speeds (e.g., slow and fast fashion speed) within a product's entire lifecycle in order to design effective circular fashion products.…”
Section: Design For Circular Production Processesmentioning
confidence: 99%